The Effect of Animation Video Education on Menstrual Hygiene Management Knowledge in Students at SMP Negeri 1 Gorontalo - Maryam Ali; Ridha Hafid; Dewi Suryaningsih Hiola (Universitas Muhammadiyah Palu, 2026)
Menstrual hygiene management is the practice of maintaining personal hygiene during menstruation to prevent the risk of infection in adolescent girls. To optimize this knowledge, interesting and easy-to-understand health education such as the use of animated videos is needed. This study aims to determine the effect of animation video education on menstrual hygiene management knowledge in female students at SMP Negeri 1 Gorontalo. This study uses a quantitative approach with a pre-experimental one-group pre-test post-test design. The population in this study is all students of SMP Negeri 1 Gorontalo who have experienced menstruation as many as 470 students. The sampling technique used proportionate stratified random sampling with a sample of 47 respondents. The research instrument used a menstrual hygiene management knowledge questionnaire. The results showed that before being given education, most respondents had a sufficient level of knowledge as many as 27 respondents (57.4%), and a small number of respondents had a low level of knowledge as many as 2 respondents (4.3%). After being educated, all 47 respondents had a good knowledge level of 100%. The results of the study using the Wilcoxon signed rank test showed a p-value = 0.000 (<0.05), which indicates that there is an influence of animated video education on menstrual hygiene management knowledge in female students at SMP Negeri 1 Gorontalo. It is hoped that animation video education can be used as an alternative to health education in the school environment.